UTILIZING WHATSAPP APPLICATION AS A LEARNING MEDIA IN THE ONLINE ENGLISH CLASS - Fatimah Mulya Sari; Triadila Safitri (Journal of Research on Language Education, 2023)
WhatsApp application as the foremost prevalent application for the education field is helpful to support the online teaching and learning process. During the Covid-19 pandemic, WhatsApp application is one of the media to help students in the learning process in online classes. WhatsApp gives useful highlights such as content, call, send videos, sounds, links, locations, documents, and pictures. The purpose of this study is to know if the use of WhatsApp applications enhances English learning during online classes. In this research, a descriptive qualitative method was employed, and to gather the data the researcher used a questionnaire to collect the data. The findings supported the use of WhatsApp applications to help students in learning English during online classes, using WhatsApp to increase students’ enthusiasm for learning English, and using WhatsApp helped students to develop English skills. In conclusion, the use of WhatsApp applications is helpful for students in learning English during online classes.